The Introduction of Medication-Free Mental Health Services in Norway: An Analysis of the Framing and Impact of Arguments From Different Standpoints - Nyttingnes, Olav; Rugkåsa, Jorun (Frontiers in Psychiatry, 2021)
Introduction: Debates about coercive practices have challenged a traditional biomedical hegemony in mental health care. The perspectives of service user organizations have gained considerable ground, such as in the development of the Convention on the Rights of Persons with Disabilities. Such changes are often contested, and might in practice be a result of (implicit) negotiation between stakeholders with different discursive positions. To improve understanding of such processes, and how discursive positions may manifest and interact, we analyzed texts published over a ten year period related to the introduction of medication-free inpatient services in Norway. Methods: We conducted qualitative analyses of 36 policy documents related to the introduction of medication-free services and 79 opinion pieces from a subsequent debate. We examined discursive practices in these texts as expressions of what is perceived legitimate knowledge upon which to base mental health care from the standpoints of government, user organizations and representatives of the psychiatric profession We paid particular attention to expressions of ‘biomedical’, ‘oppositional’, ‘bureaucratic’, and ‘psy’ discourses, and how these interacted and changed during the study period (2008-2018). Results: The analysis shows how elements from oppositional discourse—most notably the legitimacy of personal experiences as a legitimate source of knowledge—entered the mainstream by being partially incorporated into bureaucratic discourse. Strong reactions to this shift, firmly based in biomedical discourse, endorsed evidence-based medicine as the authoritative source of knowledge to ensure quality care, although accepting patient involvement. Involuntary medication of those with non-response to antipsychotic medication represented a point at which discursive positions seemed irreconcilable. Conclusion: The relative authorities of different sources of knowledge remain an area of contention, and especially in determining how best to help patients who do not benefit from antipsychotics. Future non-inferiority trials of medication-free services may go some way to break this discursive deadlock.